PENGARUH DIFERENSIASI PRODUK, PERSEPSI HARGA DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN AKSESORIS PADA BENGKEL â€OCEAN AUTO WHEELSâ€ DI SEMARANG - Emy Amalya, Dian; Khasanah, Imroatul (Faculty of Economics and Business Diponegoro University, 2015)
Purchase decision is the selection of two or more alternative choice of consumers in the purchase. Every day consumers make decisions about every aspect of daily life. If consumers have a choice between making a purchase and do not make a purchase or option to use the time, then the consumer is in a position to take a decision. Consumer decisions can be influenced by several variables, in this study were analyzed through product differentiation, perception of price and location. The purpose of this study was to analyze the effect of product differentiation, perception of price and location on purchase decision.Population in this study is that consumers who buy car accessories at Ocean Auto Wheels, Ruko Puri Anjasmoro block EE 1/10, Semarang. Sample in this study was 100 consumers. Sampling technique in this study conducted by purposive sampling technique. Type is primary data. Methods of data collection using the questionnaire. Analysis technique used is multiple regression with previously tested with test instruments and classical assumption. Analyss results using multiple regression showed that : product differentiation proved influence on purchase decisions. Perception of price proved influence on purchase decisions. Location proved influence on purchase decisions